Konsumerisme sebagai Bentuk Identitas Sosial Remaja Urban Di Era Media Sosial - Nindi Aulia; Anasta Nafsi; Ani Sari Fatimah; Ayu Azra Nadhifa; Siti Aminah Caniago (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study explores the phenomenon of consumerism and the role of social media in shaping self-image and consumptive lifestyles among urban youth. Consumerism is no longer viewed merely as an economic activity but as a symbolic practice that represents social identity, status, and cultural values. Through social media, adolescents construct an idealized self-image to gain social recognition, often leading to excessive and impulsive consumption. This phenomenon is reinforced by the influence of digital trends, influencers, and the convenience of e-commerce, which collectively promote a culture of display and social conformity. However, social media also provides opportunities for self-reflection and digital literacy that can guide individuals toward more mindful and sustainable consumption patterns. Therefore, understanding symbolic consumption is essential to analyze how young people construct their identities amid the pressures of a consumer-driven digital culture. Keywords:   Consumerism, Social Media, Self-Image, Urban Vouth, Symbolic Consumption   Abstrak Penelitian ini membahas fenomena konsumerisme dan peran media sosial dalam pembentukan citra diri serta gaya hidup konsumtif di kalangan remaja urban. Konsumerisme tidak lagi dipandang sekadar aktivitas ekonomi, melainkan sebagai praktik simbolik yang merepresentasikan identitas sosial, status, dan nilai budaya. Melalui media sosial, remaja menampilkan citra diri ideal untuk memperoleh pengakuan sosial, yang sering kali mendorong perilaku konsumtif berlebihan. Fenomena ini diperkuat oleh pengaruh influencer, tren digital, serta kemudahan akses e-commerce yang menumbuhkan budaya pamer dan konformitas sosial. Namun, media sosial juga membuka peluang refleksi diri dan literasi digital yang dapat mengarahkan konsumsi ke arah lebih bijak dan berkelanjutan. Dengan demikian, pemahaman tentang konsumsi simbolik menjadi penting untuk menilai bagaimana remaja membangun identitas di tengah tekanan budaya konsumtif era digital. Kata kunci:  Konsumerisme, Media Sosial, Citra Diri, Remaja Urban, Konsumsi Simbolik